2008
DOI: 10.1038/jhh.2008.35
|View full text |Cite
|
Sign up to set email alerts
|

Should obesity be blamed for the high prevalence rates of hypertension in black South African women?

Abstract: Hypertension is highly prevalent in South Africa, resulting in high stroke mortality rates. Since obesity is very common among South African women, it is likely that obesity contributes to the hypertension prevalence. The aims were to determine whether black African women have higher blood pressures (BPs) than Caucasian women, and whether obesity is related to their cardiovascular risk. African (N ¼ 102) and Caucasian (N ¼ 115) women, matched for age and body mass index, were included. Correlations between obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…Obesity is common among black South Africans, contributing to the onset of hypertension (Puoane et al, 2002;Schutte et al, 2008). Although obesity is associated with NAFLD, a study carried out in South Africa did not find any association between the degree of obesity and severity of NAFLD in Africans (Kruger et al, 2010), possibly due to the low number of Africans (N ¼ 12) used in their study.…”
Section: Introductionmentioning
confidence: 92%
“…Obesity is common among black South Africans, contributing to the onset of hypertension (Puoane et al, 2002;Schutte et al, 2008). Although obesity is associated with NAFLD, a study carried out in South Africa did not find any association between the degree of obesity and severity of NAFLD in Africans (Kruger et al, 2010), possibly due to the low number of Africans (N ¼ 12) used in their study.…”
Section: Introductionmentioning
confidence: 92%
“…2 It has been found that the pulse wave velocity (PWV) of muscular arteries is higher in young Africans compared with Caucasians and that there are increased levels of vascular resistance during stress. 6,[13][14][15] Increased reactions to acute psychological stress challenges are implicated in cardiovascular disease: inter alia hypertension, carotid atherosclerosis, and cardiac hypertrophy. [16][17][18][19][20][21][22] It was reported that vascular resistance reactivity in Africans was positively associated with higher α1-adrenergic receptor density and therefore a higher serum calcium sensitivity.…”
mentioning
confidence: 99%
“…Two studies by Punyadeera et al (both in 2001), found that black women have significantly less VAT than white women. Despite such findings, Joffe et al (1994), Schutte et al (2008) and Seedat et al (1983) demonstrated that obese black Southern African women have double the prevalence of diabetes (7.0% vs. 3.6%) and hypertension (30% vs. 15%) compared to obese white women who are more commonly present with coronary heart disease and hypercholesterolaemia. This suggests that SAT volume in black women may be more strongly correlated with the development of IR than in white women.…”
Section: Introductionmentioning
confidence: 91%